GAMBARAN PROFESIONALISME GURU TAMAN KANAK-KANAK DI KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Ilmi Pramestia Sundari Maolana; Wusono Indarto; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This objective of this research was to describe the professionalism of kindergarten teachers at Subdistrict Pasir Penyu Indragiri Hulu. Samples of this research is a kindergarten teacher with an educational background S1 as many 40 teachers at Pasir Penyu. Datas were gathered with quesioner that explane statemants about the professionalism the teachers of kindergarten at Subdistrict Pasir Penyu Indragiri Hulu. The conclution of this reserch that professionalism of kindergarten teachers at Subdistrict Pasir Penyu Indragiri Hulu on catagorie very high 83.44%, for the indicator design and plan learning programs obtain the percentage of 78.9% on catagorie high, indicators develop learning programs obtain the percentage of 89.25% on catagorie very high , the indicator to manage the implementation of learning programs obtain a percentage of 89.88 % on catagorie very high , the indicator assessing the learning process and results obtained percentage 79.93% with high criteria and indicators to diagnose the factors that influence the success of the learning process of obtaining the percentage of 83.8% on catagorie very high. This mean showing that kindergarten teachers have excellent professionalism.Key Words : professionalism of kindergarten teachers